Emerging dynamics of evidence and trust in online user-to-user engagement: the case of 'unproven' stem cell therapies. Issue 3 (27th May 2018) - Datta, Saheli
Abstract: This article explores the ways in which patients and their families (hereafter referred as 'users') share and evaluate disease-specific evidence via online communities. The aim is to understand what this user engagement in healthcare and knowledge production reveals about society's shifting perceptions of trust in the institutions of 'evidence-based medicine' (EBM) such as regulators, bioethicists and scientists and the implications for EBM. To do this, I use the case of experimental stem cell therapies (eSCTs). ESCTs are commonly labelled in academic literature as 'unproven', a label that frames their lack of conclusive clinical evidence as unsafe, inefficacious and thus unethical when clinically used. Despite this framing, users engage with other users to share and evaluate all available evidence for themselves, including on-going clinical trial and experiential evidence to build trust for and undertake eSCTs. Increasingly, this user engagement with evidence takes place in online communities that range from user-created and user-run Facebook pages to user-to-user discussion forums on healthcare provider sites or blogs with little if any provider-input in conversations. In this paper, I draw on a sample of these user conversations to show the complex and unpredictable ways in which what counts as evidence and how trust is built for it are shifting. In so doing, I reflect on the shifting relations between the institutions of EBM and society for greater control over evidence that lies at the heart of the evidentiary basis of public health policies.